Representations of the “image” of Aesop in recent publications of Greco-Latin fables (El Hilo de la Fabula, 2022)
The "image" of Aesop has been crystallized in different texts since classical antiquity as a figure associated with "popular" literature and, therefore, the collections of fables attributed to him went through (and still go through) a complex history of transmission and transformation. In this history, the figure of Aesop as a fabulist has been modalized according to each sociohistorical context in which his fables were recreated. The notion of "image" (Lefevere, 1992) refers to the representations that each era of humanity, through the rewriting of canonical texts, builds of each writer. Also, the notion establishes a dialogue between the ancient sculptural representations, the descriptions in the Graeco-Latin texts and the illustrations of Aesop that most publications of recent fables contain. In this paper we propose to analyze two books of fables attributed to Aesop published in Argentina: Aesop. Fábulas (Ed. Página 12) and Fábulas y antifabulas by Graciela Repún and Enrique Melantoni (2013, Ed. Uranito) because they themselves make up a ‘corpus’ of analysis as they present Aesop as "character" and "narrator". We aim to describe the textual and paratextual operations used in the construction of Aesop as a character/narrator and/or author of fables in these publications in order to problematize the relations of the Greco-Latin fable genre with the current genres of children's literature and didactic materials.
Keywords: Greco-Latin Fable; Aesop; Children's literature; Renarration-Classical tradition